Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Discovery Learning pada Pembelajaran IPAS di Kelas V SDN 20 Gumarang (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to describe the improvement of student learning outcomes using the discovery learning model in science and technology learning in Class V of SDN 20 Gumarang. This research is classroom action research in four stages, namely planning, implementation, observation, and reflection. Research data was obtained from the results of planning, implementation, and observation using the Discovery Learning model. The data collection techniques are test and non-test. The subjects of the study were teachers and students of class V of SDN 20 Gumarang, Palembayan District, Agam Regency, totaling 30 people. The results of the study show that the assessment of the teaching module in the first cycle, which is 83.34% (B), increased in the second cycle to 94.44% (SB). The assessment of teacher activity in the first cycle was 83.32% (B), increasing in the second cycle to 97.22% (SB). The assessment of student activities in the first cycle was 79.16% (C), increasing in the second cycle to 97.22% (SB). The learning outcomes of students in the first cycle were obtained on average in attitude aspects, namely 82.98 (B), knowledge was 73.83 (C), and skills were 69.46 (D). increased in the second cycle obtained an average of 84.5 (B) in attitude, 82.33 in knowledge and 81.56 (B) in skill. Thus, it can be concluded that the Discovery Learning model can improve the learning outcomes of students in science and science learning in class V of SDN 20 Gumarang, Palembayan District, Agam Regency